The Effect of Schema-Based Instruction to Improve Mathematics Problem-Solving Ability of Elementry Students - Monica Bellandina Abolla; Yurniwati Yurniwati; Faisal Madani (Elementary Teacher Education Program, Majalengka University, 2024)
Mathematical problem-solving ability is one of the skills that need to be taught to students since learning in elementary school. Mathematical problem-solving ability can be known from students' understanding of the information known and asked in the problem. They are also expected to be able to plan problem-solving strategies and perform appropriate calculation operations. Fifth-grade students of public elementary schools in Kupang City, East Nusa Tenggara still have difficulty solving problem solving problems. For this reason, the Schema Based Instruction (SBI) method was applied to improve students' mathematics problem-solving skills. This study aims to determine the effect of the SBI method on the mathematical problem-solving ability of fifth-grade elementary school students. This research used an experimental method with research design is posttest-only control group design. The research was conducted in class V in one of the public schools in Kelapa Lima District, Kupang City, NTT. The research instrument was a post-test question in the form of an essay of six numbers. The post-test results were tested using the T-test and post-hock to determine whether there was an effect of the SBI method on mathematical problem-solving skills. The calculation results show that the learning outcomes of students who learn using the SBI method are higher than students who learn using the expository method. It can be concluded that the SBI method can be used as one of the references for learning methods that can be used in learning mathematics in elementary schools to improve mathematical problem-solving skills. Keywords: Schema Based Instruction, Mathematics Problem-Solving Ability, Elementry School